Aging‐related anorexia and its association with disability and frailty - Kota Tsutsumimoto; Takehiko Doi; Hyuma Makizako; Ryo Hotta; Sho Nakakubo; Keitaro Makino; Takao Suzuki; Hiroyuki Shimada (Wiley, 2018)
Abstract Background Anorexia of ageing may be a precursor to various geriatric syndromes. We elucidated whether anorexia of ageing had a significant impact on incident disability and investigated whether anorexia of ageing had a direct association with future disability or an indirect association with disability via frailty. Methods This study employed an observational, longitudinal, cohort design in a community setting. Participants were 4393 older adults (75.9 ± 4.3 years). Anorexia of ageing was assessed by a simplified nutritional appetite questionnaire. Frailty was operationalized as slowness, weakness, exhaustion, low physical activity, and weight loss. Participants who had none of these characteristics were considered robust, those with one or two characteristics were considered pre‐frail, and those with three or more characteristics were considered frail. We examined sociodemographic variables (age, sex, and education), medical history (medication and chronic disease history), lifestyle factors (smoking and drinking habits and living arrangement), body mass index, blood nutrition data, depressive symptoms, physical functioning, and cognitive functioning. Results The prevalence of anorexia of ageing was 10.7% (n = 468). The proportion of physical frailty, pre‐frailty, and robustness were 8.4, 52.0, and 39.6%, respectively, in the without anorexia of ageing group, and 20.3, 57.7, and 22.0%, respectively, in the anorexia of ageing group (P < 0.001). During a 2‐year follow‐up, the prevalence proportion of disability was 5.6% in the without anorexia of ageing group and 10.7% in the anorexia of ageing group (P < 0.001). Adjusted for covariates (except for frailty status), the participants with anorexia of ageing had an independently associated higher risk of incident disability compared with those without anorexia of ageing (hazard ratio: 1.43, 95% confidence interval: 1.04-1.95, P = 0.03). However, adjusted for covariates (including frailty status), anorexia of ageing was not significantly associated with incident disability (P = 0.09). Structural equation models revealed that anorexia of ageing had no direct effect on disability; however, anorexia of ageing was associated with frailty. Conclusions Older adults with anorexia of ageing had a higher proportion of frailty and a higher prevalence proportion of disability compared with those without anorexia of ageing. Although anorexia of ageing may not have a direct effect on incident disability, the structural equation model suggests an indirect relationship between anorexia of ageing and incident disability via frailty status.